Heal nodes specification improvement using modified CHEF method for group based detection point network. Issue 5 (31st May 2021) - AR, Suhas; Priyatham M., Manoj
Abstract : Purpose: The purpose of the paper is to make use of multiple parameters namely; residual energy, closeness to centre and mobility of detection point (DP) for the selection of detection point network (DPN). In the novel method proposed, the path will have less number of DPs participating in the entire DPN. Design/methodology/approach: The proposed novel method will find out the special detection point (SDP) based on three criteria, namely, the amount of mobility for DP, the amount of remaining energy and the amount of distance between two DPs. This proposed method is an attempt to resolve the network lifetime problems during the communication of DPs over a period of time. It is developed for increasing the lifetime ratio, throughput, residual energy, number of alive nodes. Findings: The simulation results of the novel method show the improvement over the existing methods investigated based on the lifetime ratio, throughput, remaining energy and alive nodes. Practical implications: In the proposed method, the communication is done between different DPs in the network. The commutation is done using SDPs only from one cluster to another cluster. It is proposed for the implementation of energy efficient data sensing in mobile communication networks. Originality/value: It is a significant mechanism for energy efficient data sensing of one DP to another DP of different clusters in the network. The total energy consumed for a period of time by the network is significantly reduced from the novel method.